Successful selling with creative videos on social media - Nurhamida, Nurhamida; Notonegoro, Hamdan Akbar; Holisah, Holisah; Qolbi, Fatimah Nurul; Jannah, Miftahul; Subekti, Subekti; Hendra, Hendra; Septiana, Reski (Journal of Community Service in Science and Engineering (JoCSE), 2025)
In the digital era, creative video content has emerged as a powerful tool for marketing, particularly among youth who are highly engaged with technology and social media platforms. Despite this potential, many young individuals still face limitations in self-confidence and technical skills required to produce compelling promotional videos. Addressing this gap, this study investigates the effectiveness of structured training programs in enhancing youths’ competencies in creative video production. The program was designed in two core stages: first, a mentoring session aimed at delivering fundamental concepts and techniques in video-based digital marketing; second, a blind competition where participants were challenged to produce original content independently, without prior exposure to others’ work. This approach was intended to stimulate creativity, encourage authentic self-expression, and build hands-on experience with digital promotional tools. Findings from this initiative revealed notable improvements in participants’ confidence, creative thinking, and technical abilities in digital marketing. Moreover, the program fostered peer collaboration, critical feedback exchange, and the expansion of participants' social networks. In conclusion, the structured training effectively empowered youth by equipping them with relevant and transferable skills for digital entrepreneurship. This model can serve as a replicable framework for similar capacity-building efforts in creative industries and youth development programs. Di era digital, konten video kreatif telah muncul sebagai alat pemasaran yang ampuh, khususnya di kalangan anak muda yang sangat terlibat dengan teknologi dan platform media sosial. Meskipun memiliki potensi ini, banyak individu muda masih menghadapi keterbatasan dalam hal kepercayaan diri dan keterampilan teknis yang dibutuhkan untuk menghasilkan video promosi yang menarik. Untuk mengatasi kesenjangan ini, studi ini menyelidiki efektivitas program pelatihan terstruktur dalam meningkatkan kompetensi anak muda dalam produksi video kreatif. Program ini dirancang dalam dua tahap inti: pertama, sesi bimbingan yang ditujukan untuk menyampaikan konsep dan teknik dasar dalam pemasaran digital berbasis video; kedua, kompetisi buta di mana para peserta ditantang untuk menghasilkan konten asli secara mandiri, tanpa paparan sebelumnya terhadap karya orang lain. Pendekatan ini dimaksudkan untuk merangsang kreativitas, mendorong ekspresi diri yang autentik, dan membangun pengalaman langsung dengan alat promosi digital. Temuan dari inisiatif ini mengungkapkan peningkatan yang nyata dalam kepercayaan diri, pemikiran kreatif, dan kemampuan teknis peserta dalam pemasaran digital. Selain itu, program ini mendorong kolaborasi antarteman, pertukaran umpan balik kritis, dan perluasan jaringan sosial peserta. Sebagai kesimpulan, pelatihan terstruktur ini secara efektif memberdayakan anak muda dengan membekali mereka dengan keterampilan yang relevan dan dapat dipindahtangankan untuk kewirausahaan digital. Model ini dapat berfungsi sebagai kerangka kerja yang dapat direplikasi untuk upaya pengembangan kapasitas serupa dalam industri kreatif dan program pengembangan pemuda.